Varnostna prizadevanja Evropske unije - Malešič, Marjan (Teorija in praksa, 2016)
European Union security efforts are strengthening and accordingly the analysis checks the level of their support among the European public. The analysis focusses on two issues: The formation of the EU's common security and defence policy, and the development of a mechanism to provide and coordination of aid in of disasters. The analysis is guided by data obtained by the Eurobarometer and Slovenian Public Opinion surveys. The descriptive use of the data offers an insight into the basic standpoints, opinions and beliefs of the European and particularly the Slovenian public about the EU's security efforts. The results display high public support for those efforts, but at the same time reveal the public is not well informed about security issues. They also show some controversies. According to the public, the decision-making process on security issues should take place in EU institutions whereas the latter insist on a common security and defence policy as an inter-governmental process. Further, the public gives relatively strong support for traditional military missions (defence of the EU territory and provision of peace in the EU) whereas in practice the EU performs crisis management, humanitarian and peace operations outside its territory. On the other hand, a "future European Army" that could perform traditional military tasks lacks sufficient public support. Finally, the public is relatively poorly informed about the EU's civil protection mechanism yet at the same time gives high support for its activities.
Keywords: civilna zaščita; Crisis management; European Security and Defence Policy; European Union; Evropska unija; Evropska varnostna in obrambna politika; Javno mnenje; Krizno upravljanje; obrambna politika; Public opinion; Slovenia; Slovenija; varnostna politika